2022
DOI: 10.3390/ijerph191610249
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Understanding of the Urban Heating Problem and Mitigation: A Conceptual Framework for Urban Planning

Abstract: With the global acceleration of urbanization, temperatures in cities are rising continuously with global climate change, creating an imminent risk of urban heat islands and urban heating. Although much research has attempted to analyze urban heating from various perspectives, a comprehensive approach to urban planning that addresses the problem is just beginning. This study suggests a conceptual framework for multidisciplinary understanding of urban heating by reviewing 147 selected articles from various field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 159 publications
0
2
0
Order By: Relevance
“…The indicators of open public spaces and urban density also demonstrate significant dependence and influential potential, contributing to their effectiveness (Ahmad et al, 2019). Open public spaces play a crucial role in mitigating or reducing the intensity of SUHI by creating ventilation spaces and facilitating wind flow (Lee and Kim, 2022). An increase in density, marked by taller buildings, reduces the height-to-width ratios of streets to buildings and reduces vegetation coverage, correlated with heightened magnitudes of SUHIs (Chapman et al, 2018).…”
Section: Interpretation Of the Map Of Indicators' Typologiesmentioning
confidence: 99%
“…The indicators of open public spaces and urban density also demonstrate significant dependence and influential potential, contributing to their effectiveness (Ahmad et al, 2019). Open public spaces play a crucial role in mitigating or reducing the intensity of SUHI by creating ventilation spaces and facilitating wind flow (Lee and Kim, 2022). An increase in density, marked by taller buildings, reduces the height-to-width ratios of streets to buildings and reduces vegetation coverage, correlated with heightened magnitudes of SUHIs (Chapman et al, 2018).…”
Section: Interpretation Of the Map Of Indicators' Typologiesmentioning
confidence: 99%
“…Their studies mainly include the following three aspects: (1) exploring surface temperature's spatial distribution characteristics in established high-density communities [3], (2) analyzing the influence of spatial morphological parameters on the land surface temperature [4], and (3) proposing planning measures to mitigate the urban heat island effect. Based on determining the mechanism of urban spatial morphological parameters' influence on thermal environments, this study explores feasible solutions for optimizing the thermal environment regarding planning and implementation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Urban green spaces, for instance, mitigate the urban heat island effect and potentially reduce heatwave-related mortality rates. Studies have shown that increasing urban greenery can lower local temperatures by up to 5°C, 4 significantly impacting heatwave-induced mortality, which can rise by 7.9% with every 1°C increase in temperature. 5 Furthermore, these green spaces provide essential areas for physical activity and mental health improvement, contributing to the overall well-being of urban residents.…”
mentioning
confidence: 99%